Alkaloids from Cryptocarya densiflora Blume (Lauraceae) and their cholinesterase inhibitory activity - Wan Othman, Wan Nurul Nazneem; Sivasothy, Yasodha; Liew, Sook Yee; Mohamad, Jamaludin; Nafiah, Mohd Azlan; Ahmad, Kartini; Litaudon, Marc; Awang, Khalijah (Elsevier, 2017)
(−)-Desmethylsecoantofine N-oxide (1), a new seco-phenanthroindolizidine alkaloid along with prodensiflorins A and B (2-3), two new proaporphine alkaloids, were isolated from the leaves of Cryptocarya densiflora Blume. Their structures were established on the basis of 1D and 2D NMR techniques and LCMS-IT-TOF analysis. (+)-N-methyllaurotetanine (4), (+)-laurotetanine (5), (+)-nornantenine (6), crychine (7), (−)-isocaryachine (8), (+)-reticuline (9), (−)-desmethylsecoantofine (10), (+)-oridine (11), dicentrinone (12) and (−)-antofine (13) were also isolated with compounds 4, 7–9 and 12–13 being characterized for the first time in this plant. Compounds 1-3 were moderate to weak AChE and BChE inhibitors while compound 10 was a DPPH free radical scavenger.